Systemic granulocyte colony-stimulating factor (G-CSF) enhances wound healing in dystrophic epidermolysis bullosa (DEB): Results of a pilot trial - Fine, Jo-David; Manes, Becky; Frangoul, Haydar (Journal of the American Academy of Dermatology, 2015)
Chronic nonhealing wounds are the norm in patients with inherited epidermolysis bullosa (EB), especially those with dystrophic EB (DEB). A possible benefit in wound healing after subcutaneous treatment with granulocyte colony-stimulating factor (G-CSF) was suggested from an anecdotal report of a patient given this during stem cell mobilization before bone-marrow transplantation. We sought to determine whether benefit in wound healing in DEB skin might result after 6 daily doses of G-CSF and to confirm its safety. Patients were assessed for changes in total body blister and erosion counts, surface areas of selected wounds, and specific symptomatology after treatment. Seven patients with DEB (recessive, 6; dominant, 1) were treated daily with subcutaneous G-CSF (10 μg/kg/dose) and reevaluated on day 7. For all patients combined, median reductions of 75.5% in lesional size and 36.6% in blister/erosion counts were observed. When only the 6 responders were considered, there were median reductions of 77.4% and 38.8% of each of these measured parameters, respectively. No adverse side effects were noted. Limitations include small patient number, more than 1 DEB subtype included, and lack of untreated age-matched control subjects. Subcutaneous G-CSF may be beneficial in promoting wound healing in some patients with DEB when conventional therapies fail.